THE EFFECT OF SECOND WAVE COVID-19 CONCERNS ON DISTRESS ON MILLENNIALS PARENTING - Eka Mariyanti; Nor Azilah Husin; Puti Embun Sari; Siska Lusia Putri (Journal of Islamic, Social, Economics and Development, 2021)
The second wave of the COVID-19 pandemic in Indonesia has increased theconcerns of many people, coupled with the imposition of restrictions on community activities(PPKM) in the city of Padang, causing social and economic turmoil, which has causedtremendous pressure for many families, especially for working millennial parents. Expertswarn that a minority of people may experience long-lasting mental health problems such asdepression, anxiety, and stress longer than the pandemic itself. Previous studies with pandemicoutbreaks have shown that media attention can increase anxiety and mental fatigue. Socialisolation and restrictions on social activities can lead to improved online communication, andparents who use social media can be influenced by other people's emotions online. DuringWork From Home (WFH), the rate of meeting further people decreases. Indirectly, someMillennials parenting will spend their time with the virtual world. A lot of sad news shared onsocial media also has a significant impact on parents' mental health. The current study aimsto examine COVID-19 concerns about Distress (Depression, Anxiety, and Stress) in millennialparents. Data were collected by online surveys advertised on social media with a samplingmethod using purposive sampling with the criteria of Millennials born in 1980-1991. Havingchildren and living in the city of Padang, the sampling method used the help of the G*Powersoftware and found 147 samples as respondents in this study. Data analysis by looking at themodel and moderation using SEM-PLS. The results of the study prove that it turns out thatCovid-19 worries do not make millennial parents in the city of Padang become stressed anddepressed. The results only demonstrate that Covid-19 concerns only make millennial parentsanxious.